Evaluation of occupational safety courses given in undergraduate departments in turkey and investigation of the effect on working life - (:unkn) unknown (My University, 2023)
In this study, using the general survey model, which is one of the quantitative research methods, the evaluation of the occupational safety courses given in undergraduate departments in Turkey and their effects on working life were examined for 440 people who received their undergraduate education and started their working life. An appropriate sampling method was preferred in the sample selection of the study. According to the research, the effect of occupational health and safety courses on working life, the contribution of occupational health and safety education, and occupational health and safety education’s contribution to awareness show significant differences according to age, gender, department, and work experience. When the relationship between them is examined, these relationships are positive and moderate. The results and survey average scores show that the theoretical courses on occupational health and safety in undergraduate programs of universities in Turkey are insufficient and should be supported by practice and training in working life.
Keywords: Matematik; İstatistik; Temel Bilimler; Mathematics; Statistics; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; MATEMATİK; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MATHEMATICS; MULTIDISCIPLINARY SCIENCES; Mantık; Geometri ve Topoloji; Ayrık Matematik ve Kombinatorik; Multidisipliner; Fizik Bilimleri; Logic; Geometry and Topology; Discrete Mathematics and Combinatorics; Multidisciplinary; Physical Sciences